Heart rate variability, QT variability, and electrodermal activity during exercise - Boettger, S.; Puta, C.; Yeragani, V. K.; Donath, L.; Müller, H. J.; Gabriel, H. H. W.; Bär, K.-J. (Medicine & Science in Sports & Exercise, 2010)
Purpose: Various measures of autonomic function have been developed, and their applicability and significance during exercise are controversial.